Injectable aesthetic procedure in microveses: sclerotherapy with glucose (Research, Society and Development, 2022)
This study aimed to evaluate and describe the factors of sclerotherapy with glucose in the treatment of telangiectasias, as well as to compare the effectiveness of 75% glucose with 50% glucose. An integrative literature review study, with a qualitative approach, was prepared from academic search sites in scientific journals, academic articles, dissertations and monographs, through qualitative research in the databases: Latin American and Caribbean Literature in Science of Health (LILACS), Virtual Health Library (BVS) and National Library of Medicine (PubMed). Employing the subsequent inclusion parameters: complete articles with publications from the year 2017 to 2022, in Portuguese, English and Spanish, using the following descriptors, registered in the DeCS (Descriptors in Health Sciences): Sclerotherapy, sclerotherapy with glucose and telangiectasias. And as exclusion criteria: duplicate and incomplete articles, those that were not published in the last five years and those that were not related to the theme. The articles used were published between 2017 and 2022, with 2 articles published in 2017 (16.7%), 1 published in 2018 (8.3%), 1 published in 2019 (8.3%), 2 published in 2020 (16.7%), 5 published in 2021 (41.7%) and 1 published in 2022 (8.3%). That the use of this technique proved to be an effective alternative in the treatment of telangiectasias, with a 75% glucose concentration being more efficient in relation to a 50% glucose concentration, thus requiring more applications. In addition to presenting discomfort to the patient such as pain and burning.